Design and Development of Solar Powered Compost Bin - Munsawaeng, Ratchaneewan (RMUTL Journal of Socially Engaged Scholarship, 2023)
This paper proposes a design and a development of solar powered compost bin for solving the garbage disposal problem by mixing food scraps with materials such as leaves, sawdust, rice husks, and manure. There is using a lawn mover to mix them well with spindle. As the consequence, the nutrient soil (fertilizer) can be used for planting. The natural fermentation process is to add the air into the tank by the pump to make them flow. As well as, using the motor to rotate steel rod with arm to mix material with the air. The microorganisms grows well also accelerate decomposition.A motor and aeration pump can be performed by solar energy. The process period of the motor and the aeration pump is 1 minute per time for 10 times in a day. From the experimentation result, it can be used on time. The fertilizer process can complete within 24 hours after fermentation. The benefit is to reduce electricity costs. In addition, there is a transfer of knowledge and a follow-up of the use result in the community and also it makes participation between the community and the University of Phayao. Furthermore, the community benefit is to use this as a role model for developing or applying this for the various uses.